THE PRIEST – AN INSTRUMENT OF THE DIVINE MERCY - BOZÂNTAN, Florin (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2016)
The Priest – An Instrument of the Divine Mercy. For the Year of Mercy, the suggested theme: "The priest – An Instrument of Divine Mercy", needs to be understood from both consecrated and Christian life point of view, since we are all part of the priesthood of Christ, both the sacramental or ministerial priesthood and the common priesthood or the priesthood of the faithful. When proclaiming the Year of Mercy, Pope Francis explained how it is possible for any of us to receive and offer mercy. Therefore, I shall try to present some aspects of mercy that the clergy must be aware of, must live and put into practice. Thus, the priest is first called to make known the Word of God, and only when the Word of God becomes a spiritual food for him he may begin the new evangelization of those who knew Him or of those who have forgotten what it means to be a Christian. Secondly, one needs to consider the practicality of the teachings of the Word of God, the priest must find ways to put into practice the material and spiritual acts of mercy, and thus the Gospel becomes “operative through charity”. Last but not least, one needs to seek the Mercy of God in the sacrament of Reconciliation, where the priest finds himself to be the first penitent who received the Divine love, forgiveness and mercy, and then in turn he can provide the forgiveness of God to others, becoming a “channel” for the descent of the Mercy of God. These three ways are found in the documents of the Catholic Church, i.e. Misericordiae vultus, Dives in misericordia and Misericordia Dei, inviting us to receive and live out the Divine mercy at the true value of the love and forgiveness of the Heavenly Father. REZUMAT: Preotul, instrument al milostivirii divine. Fiind în acest An al milostivirii, această temă propusă „Preotul, instrument al milostivirii divine” trebuie înţeleasă atât din punct de vedere al persoanei consacrate cât şi al creştinului, doarece cu toţii facem parte din preoţia lui Hristos, atât preoţia sacramentală sau ministerială, cât şi preoţia comună sau a credincioşilor. Papa Francisc atunci când a declarat Anul milostivirii, a explicat cum fiecare dintre noi poate să primească dar şi să dăruiască milostivirea. Astfel în cele ce urmează am încercat să prezint câteva puncte ale milostivirii pe care preoţii trebuie să le cunoască, să le trăiască şi să le practice. Astfel, în primul rând preotul este chemat de a face cunoscut Cuvântul lui Dumnezeu, după ce acesta devine o hrană spirituală pentru el, apoi să se facă o nouă evanghelizare acelor care nu l-au cunoscut sau pentru cei care au uitat ce înseamnă a fi creştin. În al doilea rând este aplicabilitatea învăţăturilor Cuvântului lui Dumnezeu, a pune în practică faptele milosteniei trupeşti şi sufleteşti, astfel Evanghelia devenind „operantă prin caritate”. Şi nu în ultimul rând, a căuta milostivirea lui Dumnezeu, în sacramentul reconcilierii, unde preotul trebuie să fie primul penitent care primeşte iubirea, iertarea şi milostivirea divină, pentru ca apoi la rândul său acesta (preotul) să poată oferi iertarea lui Dumnezeu, preotul fiind „canalul” prin care coboară milostivirea Tatălui. Aceste trei căi numerate se regăsesc în documentele Bisericii Catolice, Misericordiae vultus, Dives in Misericordia şi Misericordia Dei, care ne cheamă la a primi şi a trăi milostivirea divină la adevărata valoare a iubirii şi a iertării Tatălui Ceresc. Cuvinte cheie: preot, milostivire, cuvântul lui Dumnezeu, sacramentul reconcilierii, mila trupească şi sufletească